Violencia obstétrica: percepción de las usuarias sonorenses - Figueroa-Palomino, Osmar Efrén (Universidad de Sonora, 2019)
Introduction: Pregnancy is a stage in which women are vulnerable, so care within hospital institutions during childbirth has a significant impact on their physical and mental health. Obstetric violence is one that is exercised within health institutions against pregnant women during childbirth care, and is still an important public health problem in Mexico. Objective: The objective of the present study is to know the perception of the users of the health services about the existence of obstetric violence. Methodology: Quantitative, descriptive study. The type of sampling was for convenience through the snowball technique, 45 participants were included. The data collection was through the Test to denounce obstetric violence in hospitals in Extremadura, adapted to the Mexican population, consists of 11 dichotomous questions. Results: 37.7% of the surveyed women perceived some type of obstetric violence by health personnel. The order of not walking (51.1%), criticism of crying or screaming (44.4%), being unable to express fears or concerns (37.8%), nicknames or diminutives (28.9%), deny changes in position and deny contact with the newborn (26.7%) and ironic comments, disqualifying, jokes (22.2%). Conclusions: Although the highest percentages are not inclined to affirmative in relation to actions considered as acts of obstetric violence, it is of great relevance to emphasize that these acts are present in considerable percentages.